Effect of the lipophilicity of endocannabinoid peptides on qsar studies in the modulation at Cb1 receptors - Zamora Ramírez, William J. (2023)
The endocannabinoid (EC) system is a neuromodulatory pathway that consists of two G protein-coupled receptors, CB1 and CB2 which can be activated by a distinct and diverse number of compounds such as N-arachidonoylglycerol (2-AG), anandamide, phytocannabinoids, and a series of peptides derived from hemoglobin known as endocababionod peptides (pepcans). Here, we analyzed the impact of several hydrophobicity scales of amino acids for describing the lipophilicity of seven endocannabinoid peptides in order to perform QSAR studies that correlate the lipophilicity of peptides with the experimental inhibitor constants to CB1 human receptors. The results indicate that the use of a state-of-the-art lipophilicity scale (ProtL scale) for describing the lipophilicity of peptides which takes into account the local-context dependency of the conformations of peptides but also the pH of the environment outperforms the results obtained with other experimental scales which only consider sequence-based information. Finally, our findings point out that is more valuable to know when and where to use a lipophilicity scale, instead of evaluating which is better or not, as they all have useful information on particle conditions and environments.